PAHs Pollution and Spatial Distribution in Agricultural Soils of Dongguan - Jin Ma; Xinghua Qiu; Zhou, Yongzhang; Zhu, Tong (Acta Scientiarum Naturalium Universitatis Pekinensis, 2011)
Investigation on PAHs in agricultural soils in Dongguan, South China were conducted. A total of 59 agricultural soil samples were collected from sites representative of the region for analysis of contents of 16 PAHs. Results show that 13 PAHs were detected with detectable ratios above 90%, Fie, Phe, Chr and Bbf were detected in all 59 samples, the detectable ratio of Ant was the lowest (13.56%). Sigma PAHs in soil samples is ranged from 29 to 2184 mug/kg, and 44.07%, 8.47% and 3.39% soil samples were slightly, moderately and heavily polluted by PAHs, respectively. Compared with other regions, Dongguan city is higher in soil PAHs contents, which can be confirmed that the increase of PAHs in agricultural soils is connected with human activities closely. Principal component analvsis demonstrate that the above-said 16 PAHs in agricultural soils may have three major contributors, corresponding to biomass burning, volatilization of oil production, and coal burning respectively. It is found that environmental factors (temperature, humidity), soil characters (pH, organic materials) and other pollutants (heavy metals) can affect environmental behaviors of PAHs. By means of ordinary Kriging interpolation, spatial distribution of 16 PAHs were studied. The results indicate that 16 PAHs vary greatly in spatial distribution between types, PAHs contents in west-north soils are much higher than that in south-east soils, and the highest PAHs contents area is in Wangniudun town, which hint that there are some pollutant sources connected with poisonous wastes combustion.